1996
DOI: 10.1103/physrevlett.77.4326
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Nonlinear Frequency Conversion with Maximal Atomic Coherence

Abstract: We demonstrate efficient nonlinear frequency conversion in atomic Pb vapor under conditions where the linear susceptibility and the effective nonlinear susceptibility are of the same order. This is accomplished by using electromagnetically induced transparency to prepare a near-maximal atomic coherence on a Raman transition. This strongly driven transition is used to convert an intense laser beam from 425 to 293 nm with an efficiency of ϳ40%. [S0031-9007(96)01644-4]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
179
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(181 citation statements)
references
References 15 publications
1
179
0
1
Order By: Relevance
“…An interesting situation is found when one of the two systems of the double-configuration is far detuned from the one photon resonance. In this case, considering the continuous wave regime, it has been shown that the total light intensity is weakly absorbed during the propagation [38,39], while the intensity of each mode oscillates sinusoidally with the optical length, being the energy transferred back and forth between the two probe beams. Later, a similar result was obtained in the quantum regime [40], where a single photon coupled initially to one of the transitions of the double-system oscillates during propagation between the two frequency modes, thus creating a superposition state at certain positions in the medium with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting situation is found when one of the two systems of the double-configuration is far detuned from the one photon resonance. In this case, considering the continuous wave regime, it has been shown that the total light intensity is weakly absorbed during the propagation [38,39], while the intensity of each mode oscillates sinusoidally with the optical length, being the energy transferred back and forth between the two probe beams. Later, a similar result was obtained in the quantum regime [40], where a single photon coupled initially to one of the transitions of the double-system oscillates during propagation between the two frequency modes, thus creating a superposition state at certain positions in the medium with high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…This allows a nearresonant probe field to experience extreme nonlinearities, while simultaneously using a second coupling field to cancel the associated absorption [1,2]. Applications include nonlinear optics at low light levels [3,4,5,6], full frequency conversion in distances so short that phase matching is not relevant [7,8,9], and quantum information storage [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Now assuming the drive field to be strong |Ω c | |Ω p |, |Ω m | and ∆ p = ∆ m , let us solve Eqs. (9)(10)(11) in steady state regime (˙ ab =˙ ac =˙ cb = 0). We obtain,…”
Section: Introductionmentioning
confidence: 99%
“…Such systems can exhibit quantum coherence and interference effects, e.g., enhanced nonlinear effects [1], electromagnetically induced transparency (EIT) [2][3][4], giant Kerr nonlinearity [5][6][7], lasing without inversion [8][9][10], efficient nonlinear frequency conversions [11,12], coherence Raman scattering enhancement via maximum coherence in atoms [13] and molecules [14], enhanced lasing [15,16], coherent Raman umklappscattering [17], photodesorption [18] to name a few. Recently quantum coherence effects has been applied to a new domain on plasmonics and shown to benefit nanophotonics [19,20].…”
Section: Introductionmentioning
confidence: 99%